Factores que inciden en una adecuada impermeabilización del concreto (2020)
Waterproofing is the process to coat and protect elements in the building that must be kept dry, protect users from the different effects of the outdoor environment and improve service conditions of each structure. Waterproofing is linked to the concept of service because it allows to preserve the initial properties of the structural elements that make up it.